WSB1: from homeostasis to hypoxia. Issue 1 (December 2016) - Haque, Moinul; Kendal, Joseph; MacIsaac, Ryan; Demetrick, Douglas
Abstract Thewsb1 gene has been identified to be important in developmental biology and cancer. A complex transcriptional regulation ofwsb1 yields at least three functional transcripts. The major expressed isoform, WSB1 protein, is a substrate recognition protein within an E3 ubiquitin ligase, with the capability to bind diverse targets and mediate ubiquitinylation and proteolytic degradation. Recent data suggests a new role for WSB1 as a component of a neuroprotective pathway which results in modification and aggregation of neurotoxic proteins such as LRRK2 in Parkinson's Disease, via an unusual mode of protein ubiquitinylation. WSB1 is also involved in thyroid hormone homeostasis, immune regulation and cellular metabolism, particularly glucose metabolism and hypoxia. In hypoxia, wsb1 is a HIF-1 target, and is a regulator of the degradation of diverse proteins associated with the cellular response to hypoxia, including HIPK2, RhoGDI2 and VHL. Major roles are to both protect HIF-1 function through degradation of VHL, and decrease apoptosis through degradation of HIPK2. These activities suggest a role forwsb1 in cancer cell proliferation and metastasis. As well, recent work has identified a role for WSB1 in glucose metabolism, and perhaps in mediating the Warburg effect in cancer cells by maintaining the function of HIF1. Furthermore, studies of cancer specimens have identified dysregulation ofwsb1 associated with several types of cancer, suggesting a biologically relevant role in cancer development and/or progression. Recent development of an inducible expression system forwsb1 could aid in the further understanding of the varied functions of this protein in the cell, and roles as a potential oncogene and neuroprotective protein.